Humanistic paradigm in leadership practice – a case study of a Confucian entrepreneur. Issue 4 (3rd July 2020) - Chou, Wan-Ju; Cheng, Bor-Shiuan
Abstract : Purpose: While current management theory is largely based on economic assumptions, there is evidence to suggest capitalism is at a crossroads. Humanistic management is accordingly proposed as an alternative new paradigm. The present study follows this approach in considering Confucianism as a humanistic practice. The purpose of this study is to explore humanistic leadership displayed by a Confucian leader and how he/she presents humanistic concern in corporate management to pursue the common good. Design/methodology/approach: This study adopted a structured–pragmatic–situational approach to conduct a case study and collected data from three sources: semi-structured interviews, consultant observations and archival data. Findings: The findings reveal that a Confucian leader takes all stakeholders' interests into account while engaging in corporate management and displays humanistic behaviors toward the stakeholders that are in line with five Confucian virtues. The leader cultivates the employees as Confucian humanistic agents. These employees accordingly act as bridges to transmit the humanistic spirit to their customers and other industries in the same market. To initiate an industry change to achieve collective welfare, a Confucian leader must first influence his/her primary stakeholders. The primary stakeholders next collectively influence the secondary stakeholders (i.e. the industry). Consequently, the overall goal of the common good is ultimately sustained. Originality/value: This study identifies valuable practical implications for humanistic practices in corporate management from a Confucian perspective. In addition, this study takes a significant academic step forward by illuminating the humanistic paradigm.